The Use of Malaysian English in the Work of Lloyd Fernando - Murooj Fareed Majeed (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The ongoing paper aims to study the use of Malaysian English lexis in creative writing by Lloyd. To be more accurate, the study aims to investigate the local language referents in the work of Lloyd Fernando in "Green is the colour". It is  a sensitive novel about racial and religious tolerance set against the shadow of the 1969 racial riot in Kuala Lumpur where four main characters, good young people from different ethnic groups who become friends and even fell in love. To give this novel a characteristic of being more realistic ,Lloyd Fernando uses lots of local words in his English novel,which lead this work to analyze these local lexis items according to categories made by Baskaran (2005).